Draft Annual Plan 1978-79 Roads and Bridges (Valley) Government of Manipur - Planning Commission (Planning Commission, 1978)
The State of Manure situated in the environment part of India is geographically landlocked. There is neither railhead nor inland water system in this State the road is the only scans of communication with other parted of the country. The National Highways No. 39 running through Nagaland Now Cash are Road are the only two roads connecting the States with the NCT of India. About 90% of the area of the State lies in a Billy terrain and the rest in the Central valley portion, terrorist, has, therefore, to be given, for the development of a sound communication system. At the time of the 1977-73 Annual Plan discussion, it was agreed that the- development of roads in world, therefore, to be examined in the light of this decision.
Government of Manipur, Public Works Department